Induction of resistance in tea plants against Sclerotium rolfsii by application of amendments and associated changes in level of phenolic content - Bhagat, Indramani (Nepalese Journal of Biosciences, 2016)
Application of neem cake,oil cake and organic amendments including cow- dung, rabbit manure and chicken manure on four varieties of tea Camellia sinensis (L.) O. Kuntze were evaluated for induction of resistance against Sclerotium rolfsii Sacc. The emphasis was on the involvement of phenolics. It was observed that total phenol levels (total phenol and ortho-dihydroxy phenols) increased in treated inoculated tea root varieties with S. rolfsii than treated uninoculated tea root varieties. Oil cake and rabbit manure induced a rapid and distinct accumulation of phenolics in contrast to neem cake, cow dung and chicken manure.